The intercommunication of the Persian and Kazakh proverbs and sayings (Journal of Oriental Studies, 2016)
Proverbs and sayings are the oldest genre of the spoken language and the creative work of the people, i.e. they are a certain mirror reflecting not only the mode of life but as well the people s history, philosophy, belief and their customs. Proverbs and sayings are being the most important of the spiritual culture and the highest form of thinking and talent have always been and will be the actual problems of the investigation. The article investigates the issue of the intercommunication of the Persian and Kazakh wisdom, philosophy which embody the true ways of people s thinking.
Keywords: Proverb; saying; genre of the spoken language